The Future of Diagnostic Radiology: Perspectives from Clinicians on Evolving Needs and Trends - Saad Zafer Algahtane,; Bandar Awad Almutairi,; Mazen Ali Alzhrani,; Motab Mesfer Alhajri,; Bader Nafe Alharbi,; Ibtesam Adan sayah Aldhafiri,; Mashael Mohammed Gharawi,; Eman Ayadah Al- enezi,; Rahaf Mohammed Alshammri,; Hadeel Dakhil Alqurashi,; Osama Fayez Ziyadi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Diagnostic radiology is undergoing a transformative period, driven by technological advancements, the rise of precision medicine, and the shift towards value-based healthcare delivery. As the field evolves, it is crucial to understand the perspectives of clinicians who rely on diagnostic radiology services to provide optimal patient care. This paper explores the evolving needs and trends in diagnostic radiology from the viewpoint of clinicians, shedding light on their expectations, challenges, and aspirations for the future of the field. Key areas discussed include the growing demand for diagnostic radiology services, the impact of artificial intelligence (AI) on the field, the drive for value-based radiology, clinicians' perspectives on the utility of radiology reports, and the future workforce landscape. The paper highlights the importance of addressing clinicians' evolving needs and expectations, such as enhancing value delivery, embracing precision medicine, integrating AI responsibly, improving communication and collaboration, addressing workforce challenges, and fostering continuous innovation and adaptability. By aligning diagnostic radiology practices with the principles of value-based care, promoting interdisciplinary collaboration, and leveraging emerging technologies, the field can position itself as an indispensable partner in delivering high-quality, personalized, and cost-effective patient care. Ultimately, the future of diagnostic radiology lies in its ability to anticipate and respond to the dynamic needs of clinicians, patients, and healthcare systems, solidifying its position as a vital component of modern healthcare delivery.